(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The modern paradigm of education involves a philosophical rethinking of the tasks of the entire education system: both general secondary and professional. Without this, any reforms and innovations are obviously unsystematic, local and fragmentary. It is safe to say that new trends in determining the role and nature of the development of the education system are of a global nature and coincide at the level of the entire world community.